Tingkat Kecemasan Atlet Dukati Taekwondo Klub Menjelang Pertandingan - Putri Galuh K; Pudjijuniarto Pudjijuniarto; Fatkur Rohman K; Made Pramono (Lembaga Pengembangan Kinerja Dosen, 2025)
The level of anxiety during competition needs to be considered because it can interfere with the athlete's focus, cause difficulty in controlling movements, reduce the quality of the game, and hinder the application of strategies, which overall has a negative impact on athlete performance. This study was motivated by the observation of researchers who found that there were still many athletes experiencing symptoms of anxiety, such as cold sweaty hands and nausea. The research method used was a survey with Nyak Amir's Sport Anxiety Scale (SAS) questionnaire consisting of 22 statement items. The subjects of this study were 20 athletes who had met the criteria and were analyzed using descriptive statistics with Microsoft Excel and SPSS. The results of the research on the anxiety of Dukati Taekwondo Club athletes before the match were in the “rather low” category with an average score of 41.25. However, if analyzed further based on aspects of anxiety, there are differences in anxiety levels in each aspect. The somatic aspect has the highest anxiety with a score of 15.5, showing physical symptoms such as heart palpitations and body trembling. Motor aspects with a score of 14.75, affective with a score of 5.45, and cognitive 5.55 were mostly in the moderate category, reflecting muscle tension, feelings of anxiety, and negative thoughts before competing.